Marketing of palay and rice in the municipality of Bugasong, Antique - Cainap, Ma. Liza Adricula .; Vios, Gregg Louie Oñate (2003.)
This study describes the marketing practices and cost, net farm price received by the producers, gross margin received by the middlemen and the problems encountered in palay and rice marketing in the Municipality of Bugasong, Antique, Primary data were gathered from 24 palay producers who were interviewed about their last harvest and ten middlemen who were interviewed about their last weeks' transactions., Of the total volume sold by the producers (164,700kg), 79.67 percent went to the wholesaler-retailer-miller. The highest price of Php9.50kg was received by the producers from the National Food Authority (NFA), an institutional buyer. The lowest price of Php6.43/kg was received from the wholesaler-retailer-millers. The marketing costs incurred were Php3.81/kg and Php4.32/kg by the producers who sold within and outside the Municipality, respectively. The depreciation of investments accounted for the largest share of marketing costs of both the producers who sold within and outside of Bugasong. The palay producers who had sold to the NFA received the highest net farm price of Php7.38/kg. The producers who sold palay to the wholesaler-retailer-millers in Bugasong and wholesaler-retailers based outside of Bugasong received the lowest net farm price of Php4.06/kg. By market function, three types of middlemen were identified: wholesaler-retailer-miller, wholesaler-retailer and retailer. The middlemen sold a total volume of 3,603,486.67kg of palay within Bugasong and 972,250.58kg of rice within (45.44 percent) ) and outside (54.56 percent) of Bugasong. The wholesaler-retailers sold the highest volume (63.45 percent) of Bugasong. The wholesaler-retailers sold the highest volume (63.45 percent) of Bugasong. The wholesaler-retailers sold the highest volume (63.45 percent) of rice. The wholesaler-retailer-millers of palay received the highest average selling price of Php8.42/kg while the retailers of rice who sold outside of Bugasong received the highest selling price of Php16.40/kg. Among the middlemen who sold outside of Bugasong, the wholesaler-retailer-millers of palay (Php1.01/kg) and wholesaler-retailers of rice (Php7.39/kg) received the highest gross margin. For those who sold within Bugasong, wholesaler-retailer-millers of rice had the highest gross margin received at Php9.10/kg. The retailers received the least gross margin at Php1.15/kg. Moreover, the wholesaler-retailers of rice who sold outside Bugasong and wholesaler-retailers of rice who sold within Bugasong received the highest net return of Php0.33/kg and Php8.22/kg, respectively. The low price of palay and rice was the main problem cried by the producers and the middlemen.
Thesis (Undergraduate, Bachelor of Arts in Economics) College of Arts and Sciences,University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Palay -- Marketing